From Antarctic prototype to ground test demonstrator for a lunar greenhouse - Maiwald, Volker; Kyunghwan, Kim; Vrakking, Vincent; Zeidler, Conrad (Acta Astronautica, 2023)
The Moon has returned into the focus of human endeavors regarding human spaceflight, e.g., with NASA's Artemis program, ESA's Moon Village, and the Russian/Chinese International Lunar Research Station. In difference to the pathfinding missions of the Apollo-era, the goal for these future missions is to stay on the lunar surface for longer durations and inhabit the lunar environment (near-)permanently. This requires a different approach to be affordable, i.e., instead of resupply as mostly used on e.g., the International Space Station, resource management has to include recycling and in-situ utilization. The former especially calls for the application of so-called BLSS to allow providing essential life-support services to the crew without prohibitive resource consumption, which is economically not feasible to achieve with resupplies. Bio-regenerative-life-support systems have been researched for decades, yet the system complexity, technology advancements, and singular aspects as e.g., plant biology require more research, especially if combined as in a greenhouse. For instance, the understanding of how a microbiome develops in a closed environment and what implications the microbiome has on plant growth is still insufficient. Within the EDEN project, the German Aerospace Center built a lunar analogue greenhouse and operated it at the Neumayer-III research station in Antarctica for four years, testing the technology – which was not space hardware – and operations. Derived from this experience the next step in the project is to design and subsequently operate a ground test demonstrator for a lunar greenhouse, as close as possible to the actual space hardware and operations. This paper explains the current design and trade-offs that led to it. Furthermore, the concept of operations is shown to illustrate the demonstrator's utility for researching bioregenerative-life-support. Overall, the system presented is feasible and useful to close the gaps, currently still existing in this field of research, and thus a mission ...